Comparative Study: Use Of 0.9% Normal Saline Irrigation Liquid and 10% Povidone-Iodine in The Process of Laparatomy Sectio Caesarea Operation in Hospital - Dedi Kurnia (Rifa'Institute, 2022)
Introduction: Operating Area Infections (IDO) is part of Healthcare-Associated Infections (HAIs) which is a global problem and reaches at least 9% (3%-21%) of 1.4 million clients worldwide. This figure was reported by the World Health Organization (WHO) from the results of a survey in 14 countries covering 28,861 clients in 47 hospitals. Based on the results of a survey every year, millions of people undergo surgical treatment so that surgical intervention covers about 13% of the total life or DALYs (Disability-Adjusted Life Years). Objective: irrigation fluids normal saline 0.9% and povidone-iodine with the wound healing process after laparotomy sectio caesarea. Methods: The design used in this study is an expost facto comparative, namely research that compares the presence of one or more variables in different samples with a retrospective approach. Results and Discussion: The results of the research analysis showed that there were significant differences between the two irrigation fluids, but according to several theories and research, the differences were due to differences in composition and characteristics of the irrigation fluids that had been used. However, the irrigation fluid can still be used for intraoperative irrigation. Conclusion: This study shows that there is a statistical difference between the two types of irrigation fluids, namely normal saline 0.9% and povidone iodine on the wound healing process by having different characteristics and fluid composition